2019
DOI: 10.1039/c9mt00035f
|View full text |Cite
|
Sign up to set email alerts
|

Functional iron deficiency in toxic milk mutant mice (tx-J) despite high hepatic ferroportin: a critical role of decreased GPI–ceruloplasmin expression in liver macrophages

Abstract: Jackson toxic milk mutant mice (tx-J) carrying a missense mutation in the Atp7b gene are animal models of the Wilson disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…observed in the organ and accordingly liver was injured. In particular, the appearance of the organ revealed with intravital microscopy was striking as sinusoids were hardly visible, and hepatocytes were enlarged and their nuclei were barely evident, a phenotype coinciding with hematoxylin-stained liver sections (33). Moreover, numerous autofluorescent bodies could be detected.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…observed in the organ and accordingly liver was injured. In particular, the appearance of the organ revealed with intravital microscopy was striking as sinusoids were hardly visible, and hepatocytes were enlarged and their nuclei were barely evident, a phenotype coinciding with hematoxylin-stained liver sections (33). Moreover, numerous autofluorescent bodies could be detected.…”
Section: Discussionmentioning
confidence: 87%
“…We revealed that at least some neutrophils express the copper transporter -CTR1, and moreover some of them express both ATP7A and ATP7B (up to 5% of neutrophils). While expression of ATP7A is anticipated in most cell types (21), ATP7B expression was so far only reported in hepatocytes and KCs (33). To the best of our knowledge, expression of ATP7 isoforms was not studied in neutrophils so far.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations